Covers and the Poetics of Communication. Issue 1 (2nd January 2021) - Kuriyama, Shigehisa
Abstract: Do covers still have a place in our digital age? The physical book has proved more resilient than champions of electronic texts once predicted, but the overall trend is plain: with each passing year we are reading less from printed paper and more on phones, tablets, e-book readers, and computers. The question this article addresses is: Do cover images still have a place when the publications that they previously covered are becoming nothing more than digital bits? By pointing out how they communicate very differently than the texts that they represent, the article argues for the continuing importance of cover images and for the need to meditate anew on the poetics of communication.